2021
DOI: 10.1016/j.tranon.2020.100948
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem/stromal cells: Developmental origin, tumorigenesis and translational cancer therapeutics

Abstract: Highlights Acknowledging the developmental origin of MSCs and the localization of MSCs in the primary tumor sites and the fetal and extraembryonic tissues is conducive to better understanding MSC contributions to the cellular origin of cancer. Several direct and/or indirect mechanisms of MSC action contribute to the cellular origin of cancer including: (i) induction of an EMT to generate cancer stem cell-like state in cancer cells; (ii) likely to act as tumorigenic progenito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 106 publications
1
51
0
Order By: Relevance
“…The main risks of MSCs are proinflammatory properties, tumorigenicity, and fibrosis [ 58 ]. Among them, tumorigenicity is the most serious and many studies have shown that MSCs have the ability to converse into tumors as well as the ability to trigger tumor development [ 59 ]. The excessive productions of cytokines by MSC, such as growth factors and chemokines, directly act on surface receptors of cancer cells, thereby regulating tumor enhancement [ 60 ].…”
Section: At-msc Collection Approaches For Treatment Of Noamentioning
confidence: 99%
“…The main risks of MSCs are proinflammatory properties, tumorigenicity, and fibrosis [ 58 ]. Among them, tumorigenicity is the most serious and many studies have shown that MSCs have the ability to converse into tumors as well as the ability to trigger tumor development [ 59 ]. The excessive productions of cytokines by MSC, such as growth factors and chemokines, directly act on surface receptors of cancer cells, thereby regulating tumor enhancement [ 60 ].…”
Section: At-msc Collection Approaches For Treatment Of Noamentioning
confidence: 99%
“…Moreover, due to the multifaceted role of MSCs in tumor progression, MSC-based anti-cancer therapies guide new strategies to overcome therapy resistance. For example, MSCs are being exploited as selective carriers for drug delivery in cancers because of their strong tropism and recruitment to tumors (Li et al, 2021). Several preclinical studies have been conducted to exploit the tumor-targeting ability of MSCs, using MSCs as an excellent in vivo vehicle to deliver tumor-killing drugs (Kim et al, 2015;Yin et al, 2018).…”
Section: Differentiating Into Caf or Cscmentioning
confidence: 99%
“…The unique properties of mesenchymal stromal/stem cells (MSCs) to self‐renew together with their and immunomodulatory characteristics have rendered MSCs attractive to researchers and clinicians as a means of cellular therapy [32–34]. The broad repertoire of secreted trophic factors (cytokines), commonly referred to as the MSC secretome, exhibiting diverse functions such as immunomodulation, anti‐inflammatory activity, angiogenesis and anti‐ apoptotic, has gained immense attention in the past few years [35].…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…The source of MSC and donor characteristics and its significance to the disease being treated, the route of administration and the dose and frequency of MSC to be administered is not known and the parameters to be monitored for clinical effectiveness are not established and often vary for different diseases. Furthermore, the long‐term safety of MSC‐based therapies remains poorly established and continues to pose a major limitation to translating MSCs into clinical practice [32,33]. In view of the above challenges, many MSC therapies have not been able to meet primary efficacy end points.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%